Sub-Saharan Africa : Growth, Savings, and Investment, 1986-93 - Muhleisen, Martin; Ghura, Dhaneshwar; Hadjimichael, Michael; Nord, Roger (Washington, D.C. : International Monetary Fund, 1995)
This paper assesses the economic performance during 1986-93 of sub-Saharan African countries as a group and of selected analytical subgroups of countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet